IMPLEMENTASI QUALITY FUNCTION DEPLOYMENT (QFD) PADA USAHA KECIL MENENGAH (UKM) ANGKRINGAN DI KOTA PALEMBANG - Maryadi, Deri; Tamalika, Tolu; Moulita, R.A. Nurul; P.O Sianipar, Togar; Suhendra (Fakultas Teknik Universitas Tridinanti, 2024)
Micro, Small, and Medium Enterprises (MSMEs), such as angkringan in Palembang City, face the challenge of enhancing product and service quality to meet rising customer expectations. Addressing this challenge is essential for maintaining competitiveness and ensuring business sustainability. This study aims to apply Quality Function Deployment (QFD) as a method to help angkringan MSMEs improve customer satisfaction and enhance business agility. By employing both qualitative and quantitative approaches, QFD is integrated into the angkringan's business processes. This involves identifying customer needs, translating these needs into specific product characteristics, and aligning them with production processes. The House of Quality (HoQ) analysis identifies several key areas for improvement, such as expanding the customer parking area, increasing seating capacity, and diversifying food product offerings. Implementing these recommendations is expected to make the angkringan a preferred choice among loyal customers, even as new angkringans emerge in Palembang.